Perlite Application and Performance Comparison to Conventional Additives in Blended Cement - Sicakova, A.; Kardosova, E.; Spak, M. (Engineering, Technology & Applied Science Research, 2020)
This study compares the performance of perlite with that of conventional additives in blended cements. The results of the application of Perlite Powder (PP) as a component of blended cements in two different proportions (30% and 50%) are presented and compared with standard additives of fly ash (FA) and Ground Granulated Blast Furnace Slag (GGBFS). Moreover, perlite is tested as a component of ternary cement (70% cement, 15% P and 15% FA and GGBFS alternatively). Blended cements are tested in terms of flexural strength, compressive strength, bulk density, water absorption, and frost resistance. The results show that although perlite blended cements achieve lower strengths and higher absorptivity compared to conventional additives, they have significant potential for freezing and thawing durability, especially in ternary combination with GGBFS. For practical applications, the intrinsic values of the parameters of the individual binders with perlite (e.g. flexural strength of 4.1–6.2MPa or compressive strength of 18.8–38.5MPa) are sufficient for many practical applications. Perlite, when suitably combined with other pozzolanic materials, can be a suitable component of blended binders.